Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = (5\(x\) + 1)2 + (5\(x\) - 1)2 - 2.( 5\(x\) +1).(5\(x\) - 1) tại \(x\) = 1
Thay \(x\) = 1 vào A ta có:
A = (5.1 + 1)2 + (5.1 - 1)2 - 2.(5.1 + 1).(5.1 - 1)
A = 62 + 42 - 2.6.4
A = 36 + 16 - 48
A = 52 - 48
A = 4
(x2-5x+1)2+2(5x-1)(x2-5x+1)+(5x-1)2
= [(x2-5x+1)+(5x-1)]2
= (x2-5x+1+5x-1)2
= (x2)2
= x4
(x2 - 5x + 1)2 + 2(5x - 1)(x2 - 5x + 1) + (5x - 1)2 = (x2 - 5x + 1 + 5x - 1)2 = (x2)2 = x4
C = ( x2 - 5x + 1 )2 + ( 5x - 1 )2 + 2( x2 - 5x + 1 )( 5x - 1 )
= [ ( x2 - 5x + 1 ) + ( 5x - 1 ) ]2 ( HĐT số 1 )
= ( x2 - 5x + 1 + 5x - 1 )2
= ( x2 )2 = x4
(125x3+1):(5x+1)
= [(5x)3+1)]:(5x+1)
=(5x+1)(25x2-5x+1):(5x+1)
= 25x2-5x+1
DỀ sai ròi kìa
P = ( 5x- 1) ^2 + 2 ( 1 - 5x) .(4+5x) + (5x+4)^2
= (5x- 1 )^2 - 2 ( 5x- 1).(5x+4) + (5x+4)^2
= (5x - 1 - 5x - 4) ^2 = ( - 5)^2 = 25
(**** )
\(=25x^2+10x+1+25x^2-10x+1+2\left(25x^2-1\right)\)
\(=50x^2\)\(+2\)\(+50x^2\)\(-2\)
\(=100x^2\)
= 100 x mũ 2